Water supply and sewerage - McGhee, Terence J. (New York : McGraw-Hill, 1991)
Introduction; Quantity of water and sewage; Hydraulics; Rainfall and runoff; Groundwater; Aqueducts and water pipes; Collection and distribution of water; Quality of water supplies; Clarification of water; Filtration of water; Miscellaneous water treatment techniques; Sewerage - general considerations; Storm water flow..
Rev. ed of: Water supply and sewerage / E.W. Steel, Terence J. McGhee.
Includes bibliographical references and index.
Keywords: Water-supply.; Sewerage; Water-supply engineering; Sewerage